Projeto e implementação de um conversor CC-CC isolado com elevado ganho estático e rendimento para aplicação em microinversores fotovoltaicos - Moraes, Cassiano Ferro (2020)
The photovoltaic generation has grown significantly worldwide, mainly due to the reduction in module prices and also in the manufacture of inverters. Among the configurations of photovoltaic inverters, the microinverter topology features some advantages for lower power applications, usually involving one or two modules. This topology generally consists of two conversion stages, and in the first one, a high voltage gain and high-eficiency DC-DC converter is demanded, which is not easy to implement. Compared to other isolated converters, the current-fed half-bridge topology presents some advantages for photovoltaic microinverters applications, such as high static gain through the transformer ratio, low input current ripple, and no unbalance in the transformer flow. In addition, the galvanic isolation reduces shock hazards and problems regarding the module's leakage current. However, similar to other isolated converters, this topology has problems related to the energy stored in the high-frequency transformer leakage inductance, which causes overvoltages across the switches when these are turned off. These voltage spikes generate higher stress, power losses, requiring semiconductors that features high breakdown voltage and also afect the reliability of the converter. Thus, this work presents the design and implementation of a current-fed half-bridge converter with the inclusion of an auxiliary circuit for active-clamping. With this circuit, it is possible to employ semiconductors with lower breakdown levels, which usually have lower conduction resistance, providing a high-eficiency to the converter, which is essential for photovoltaic microinverters applications. In addition, the auxiliary circuit reduces the switching losses, and also stress on the semiconductors, providing the increase of the switching frequency. The converter's operation, as well as the design methodology, are described. Then, the design and simulation of the proposed converter for an input power equal to 350 W are presented. After the implementation, experimental tests were performed with the prototype, and a consistent operation was verified considering the results obtained in simulation. An eficiency equals 95.8% was achieved for the designed operating point.